ANALISIS KETERAMPILAN MENGELOLA KELAS OLEH GURU SOSIOLOGI DI KELAS XI IIS 1 SMA MUJAHIDIN PONTIANAK - Aprilia, Eva; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this thesis is "Analysis of classroom management skills by sociology teachers in improving student learning outcomes in class XI IIS 1 SMA Mujahidin Pontianak". Â A common problem in this study is â€œhow about the skills in managing classes by sociology teachers in improving student learning outcomes in class XI IIS 1 SMA Mujahidin Pontianak?â€ with sub problems as follows 1) how are the skills in managing classes by sociology teachers in creating the right teaching and learning climate in class XI IIS 1 SMA Mujahidin Pontianak? 2) how about the skills in managing the class by a sociology teacher in organizing the study room in class XI IIS 1 SMA Mujahidin Pontianak? 3) how to manage class skills by sociology teachers in managing teaching-learning interactions in class XI IIS 1 SMA Mujahidin Pontianak?. This research uses qualitative research methods in the form of a descriptve. Data collection tools using the guidelines of observation, interview and dokumentation study guidelines. The research result show (1) skills in managing classes by sociology teachers in creating the right teaching and learning climate in class XI IIS 1 SMA Mujahidin Pontianak can be said good. This can be seen from sociology subject teachers in conducive classes. Both when he explained the material, question and answer session, and discussion. (2) class management skills by a sociology teacher in organizing a study room in class XI IIS 1 SMA Mujahidin Pontianak can be said good. This can be seen from the expertise of the sociology subject teacher in arranging the seating of students, arranging displays, and ensuring the class is kept clean. The class in the decor is as comfortable and beautiful as possible. (3) class management skills by sociology teachers in managing teaching-learning interactions in class XI IIS 1 SMA Mujahidin Pontianak can be said good. This can be seen from the expertise of the sociology subject teacher in leading the discussion.Keywords:Â  Classroom Management Skills, Teacher